De la beauté au devoir: esthétique de la nature et éthique environmentale - Rolston, Holmes, 1932-2025, author; Librairie Philosophique J. Vrin, publisher (Colorado State University. Libraries, 2015)
In both environmental aesthetics and environmental ethics something of value is at stake. These are often connected: If beauty, then: duty. But not all duties are tied to beauties. Other premises, such as resource use or respect for life, might better yield duties. Human aesthetic capacities depend on aesthetic properties of value. Wildlife admirers focus on animal excellences. Biotic communities, ecosystems, have their integrities. In a participatory aesthetics, an appropriate admiration for nature transforms into our caring.

See From beauty to duty - English version: http://hdl.handle.net/10217/37181.
Keywords: conservation; scenic grandeur; environmental aesthetics; environmental ethics; biotic community; nature